Respon Tanaman Jagung terhadap Cara Aplikasi dan Jenis Bakteri Endofitik Penambat Nitrogen - Setiawati, Mieke Rochimi; Maharani, Nadhira Saniya; Suryatmana, Pujawati; Hindersah, Reginawanti; Fitriatin, Betty Natalie; Chotimah, Andina; Aditya, Fasa (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
The increase in corn plant growth is greatly influenced by cultivation techniques includingfertilization. However, the use of inorganic fertilizers for a long period of time can reduce soil quality.An alternative environmentally friendly technology that can substitute for the use of inorganicfertilizers is the biological fertilizer of nitrogen-fixing endotypic bacteria. These endophytic bacteriahave benefits as growth stimulants for plants in increasing nitrogen supply through N2 fixationthrough the air. This study aims to increase the growth of corn plants through the application methodand type of nitrogen-fixing endophytic bacteria. This study used a Randomized Block Design (RBD).The treatment of types and application methods consisted of treatments without endophytic bacterialisolates, endophytic bacterial isolates Gluconacetobacter diazotrophicus Corrig, G. diazotrophicusstrain 4L, and Burkholderia gladioli with three application methods, namely seed treatment, soiltreatment, and their combinations. The results of the study showed that G. diazotrophicus 4L bacteriaapplied by seed and soil treatment gave the best effect on the growth of corn plants on the parametersof the endophytic bacterial population in leaf tissue, wet weight and dry weight of corn by 1 and 3times compared to the control and there was also a tendency to increase the dry and wet weight of thecorn plant crown.